Standardization of Small Animal Imaging-Current Status and Future Prospects. - Mannheim, Julia G.; Kara, Firat; Doorduin, Janine; Fuchs, Kerstin; Reischl, Gerald; Liang, Sayuan; Verhoye, Marleen; Gremse, Felix; Mezzanotte, Laura; Huisman, Marc C. (Molecular Imaging & Biology, 2018)
The benefit of small animal imaging is directly linked to the validity and reliability of the collected data. If the data (regardless of the modality used) are not reproducible and/or reliable, then the outcome of the data is rather questionable. Therefore, standardization of the use of small animal imaging equipment, as well as of animal handling in general, is of paramount importance. In a recent paper, guidance for efficient small animal imaging quality control was offered and discussed, among others, the use of phantoms in setting up a quality control program (Osborne et al. 2016). The same phantoms can be used to standardize image quality parameters for multi-center studies or multi-scanners within center studies. In animal experiments, the additional complexity due to animal handling needs to be addressed to ensure standardized imaging procedures. In this review, we will address the current status of standardization in preclinical imaging, as well as potential benefits from increased levels of standardization.